A novel interactive educational system in the operating room–the IE system. Issue 1 (December 2016) - Nakayama, Takayuki; Numao, Noboru; Yoshida, Soichiro; Ishioka, Junichiro; Matsuoka, Yoh; Saito, Kazutaka; Fujii, Yasuhisa; Kihara, Kazunori
Abstract Background The shortage of surgeon is one of the serious problems in Japan. To solve the problem, various efforts have been undertaken to improve surgical education and training. However, appropriate teaching methods in the operating room have not been well established. The aim of this study is to assess the utility of a novel interactive educational (IE) system for surgical education on urologic surgeries in the operating room. Methods A total of 20 Japanese medical students were educated on urologic surgery using the IE system in the operating room. The IE system consists of two parts. The first is three-dimensional (3D) magnified vision of the operative field using a 3D head-mounted display and a 3D endoscope. The second is interactive educative communication between medical students and surgeons using a small-sized wireless communication device. The satisfaction level with the IE system and the physical burden on medical students was examined via questionnaire. Results All students utilized the IE system in urologic surgery and responded to the survey. Most students were satisfied with the IE system. They also felt more welcomed by the surgeon when using the IE system than when not using it. No major unpleasant symptoms were observed but five students (25 %) experienced mild eye fatigue as a result of viewing the medical images. Conclusions The IE system has the potential to motivate students to become interested in surgery and could be an efficient method of surgical education in the operating room.